Oral History Interview with Janice Bogstad by Robin Umber - Umber, Robin E.; Bogstad, Janice Marie (My University, 2009)
This interview is part of an oral history project conducted in honor of 25th anniversary of the Women's Studies Program at the University of Wisconsin - Eau Claire.